1997
DOI: 10.1099/00221287-143-4-1243
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes in Rhizobium leguminosarum bv. trifolii whose products are homologues to a family of ATP-binding proteins

Abstract: The wild-type Streptomyces lividans 66 genome contains a 4 3 kb amplifiable DNA unit (AUD), and its four ORFs encode proteins that could not be identified by sequence comparison with databases. One of the gene products (encoded by orf-2) was purified and determined to be a novel 23 kDa protein. This protein is synthesized by the wild-type strain, absent in a variant lacking the AUD and overproduced in a variant in which the AUD is amplified (ADS). Immunological studies and analyses by confocal laser microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…ambofaciens (Leblond and Decaris, 1994; Aigle et al ., 1996) and S . lividans (Rauland et al ., 1995; Betzler et al ., 1997). The mechanism of type I amplification remains unclear.…”
Section: Requirements For Dna Amplificationmentioning
confidence: 99%
“…ambofaciens (Leblond and Decaris, 1994; Aigle et al ., 1996) and S . lividans (Rauland et al ., 1995; Betzler et al ., 1997). The mechanism of type I amplification remains unclear.…”
Section: Requirements For Dna Amplificationmentioning
confidence: 99%
“…In Streptomyces species only few surface-exposed proteins have been described up to now. These include a 23-kDa protein from Streptomyces lividans (12), a cell-bound esterase synthesized by the cyclophilin A-producing strain Streptomyces chrysomallus X2 (13), the myceliaassociated cellulase (14), catalase-peroxidase from Streptomyces reticuli (15), and the surface-active proteins (i.e. SapB from Streptomyces coelicolor and its homologue from Streptomyces tendae), which are involved in erecting aerial hyphae (16).…”
mentioning
confidence: 99%
“…Large deletions removing one or both ends of the chromosome precede the amplification events. DNA sequence analysis of amplified DNA has revealed the presence of putative genes and in a few cases gene expression was demonstrated (Aigle et al, 1996 ;Betzler et al, 1997 ; this work) but there is no indication that the amplification of these genes is of any selective advantage to the cells. Even in the case of AUD2, which encodes the mercury-resistance genes, amplification was spontaneous and not selected by adding high mercury concentrations to the medium (Sedlmeier & Altenbuchner, 1992).…”
Section: Discussionmentioning
confidence: 85%
“…A class I AUD region of about 70 kb was described by Rauland et al (1995) in 2-deoxygalactose-resistant mutants about 300 kb away from the other end of the chromosome. The 24 kb AUD3 sequence, which was found amplified together with AUD1 in a Cml S Arg -mutant (Altenbuchner et al, 1988), and a 4n3 kb sequence found by Betzler et al (1997) might be part of this AUD class I region.…”
Section: Introductionmentioning
confidence: 88%